Cluster correlation effects in 12C+12C and 14N+10B fusion-evaporation reactions - Morelli L.; Baiocco G.; D’Agostino M.; Gulminelli F.; Bruno M.; Cinausero M.; Degerlier M.; Fabris D.; Gramegna F.; Marchi T.; Barlini S.; Bini M.; et al. (EPJ Web of Conferences, 2015)
The decay of highly excited states of 24Mg is studied in fusion evaporation events completely detected in charge in the reactions 12C+12C and 14N+10B at 95 and 80 MeV incident energy respectively. The comparison of light charged particles measured spectra with statistical model predictions suggests that the dominant reaction mechanism is compound nucleus (CN) formation and decay. However, in both reactions, a discrepancy with statistical expectations is found for α particles detected in coincidence with Carbon, Oxigen and Neon residues. The comparison between the two reactions shows that this discrepancy is only partly explained by an entrance channel effect. Evidence for cluster correlations in excited 24Mg CN is suggested by the comparison between the measured and calculated branching ratios for the channels involving α particles.